Faktor-Faktor Yang Mempengaruhi Keberhasilan Usaha Pada Usaha Litha Catering Tentena - Fredrik Bastian Kawani (Fakultas Ekonomi Universitas Kristen Tentena, 2023)
This study aims to analyze the factors that influence the success of Litha Catering Tentena's business.The research method used is multiple regression analysis method, using t test and F test. The resultsshowed that partially Skills Education (X1), Technology (X2) and Capital (X3) variables were positivelyand significantly influenced on the success of Lithenta Catering Tentena. The results of F test(simultaneous significance test) concluded that the variables consisting of Kealian (X1), Technology(X2) and Capital (X3) have positive and significant influence to the success of Litha Catering EklesiaTentena.